Application of Mixed Reality in Medical Training and Surgical Planning Focused on Minimally Invasive Surgery - Sánchez-Margallo, Juan A.; Plaza de Miguel, Carlos; Fernández Anzules, Roberto A.; Sánchez-Margallo, Francisco M. (Frontiers in Virtual Reality, 2021)
Introduction Medical training is a long and demanding process, in which the first stages are usually based on two-dimensional, static, and unrealistic content. Conversely, advances in preoperative imaging have made it an essential part of any successful surgical procedure. However, access to this information often requires the support of an assistant and may compromise sterility in the surgical process. Herein, we present two solutions based on mixed reality that aim to improve both training and planning in minimally invasive surgery. Materials and Methods Applications were developed for the use of the Microsoft HoloLens device. The urology training application provided access to a variety of anatomical and surgical training contents. Expert urological surgeons completed a questionnaire to evaluate its use. The surgical planning solution was used during laparoscopic renal tumorectomy in an experimental model and video-assisted right upper lobectomy in an adult patient. Surgeons reported their experience using this preoperative planning tool for surgery. Results The solution developed for medical training was considered a useful tool for training in urological anatomy, facilitating the translation of this knowledge to clinical practice. Regarding the solution developed for surgical planning, it allowed surgeons to access the patient’s clinical information in real-time, such as preoperative imaging studies, three-dimensional surgical planning models, or medical history, facilitating the surgical approach. The surgeon’s view through the mixed reality device was shared with the rest of the surgical team. Conclusions The mixed reality-based solution for medical training facilitates the transfer of knowledge into clinical practice. The preoperative planning tool for surgery provides real-time access to essential patient information without losing the sterility of the surgical field. However, further studies are needed to comprehensively validate its clinical application.